High-power terahertz emission in magnetized plasma via optical rectification of a super-Gaussian laser beam. (18th September 2017) - Singh, Monika; Kumar, Sintu; Singh, Ram Kishor; Uma, R.; Sharma, R. P.
Abstract: The paper discusses the generation of terahertz (THz) wave via the optical rectification of an amplitude-modulated super-Gaussian laser beam in the preformed periodic density plasma when a magnetic field is applied transversely. The non-uniform spatial variation in intensity of the laser beam drives a strong ponderomotive force. Such ponderomotive force generates nonlinear oscillatory drift velocity to plasma electrons that produce a strong transverse nonlinear current at the modulation frequency (the frequency of the radiation lies in the THz domain). Moreover, the presence of the periodic density plasma structure and magnetic field can shift the condition of resonance and can produce the tunable THz frequency radiation. In the current scheme, the THz field amplitude increases with the profile index of the laser, modulation index, ripple parameters, and transversely applied static magnetic field. As a result, the efficiency of the generated THz wave can be achieved of the order of for the exact phase-matching condition.